The Relationship Between Sleep Quality and Depression in Older People Living in 3 Districts of Tehran, Iran - Ahmad BehPajooh; Simin Soleymani (University of Social Welfare & Rehabilitation Sciences, 2016)
Objectives: Most old age people are facing physical and mental problems such as movement problems, chronic pain, sleeping problems, seclusion, and depression. Thus, it is necessary to allocate a good share of health and treatment resources in any society to old age people and attend their problems. This study aimed to examine the relationship between sleep quality and the level of depression in people residing in nursing homes of 3 districts of Tehran City, Iran, in 2013. Methods & Materials: This descriptive-analytical study included people living in nursing homes of Tehran Welfare Organization. The study sample consisted of 90 older people who were selected through cluster random sampling considering the proportion of the northern, central, and southern regions of Tehran and observing their level of consciousness, ability to respond, and willingness to participate in the study. To obtain the data, we used 2 questionnaires of Pittsburgh sleep quality index and geriatric depression scale. Then, the obtained data were analyzed through multivariate regression. Results: Older women constituted 60% of the participants. The findings revealed that there was a negative and significant relationship (P<0.001) between sleep quality of the elderly people and their depression level. However, there was a positive and significant relationship (P<0.001) between the level of depression and variables of sleep disorders, using sleep aids, and disorders in daily activities. Conclusion: There is a causal and mutual relationship between sleep disturbances and depression, in such a way that sleeplessness could end in depression, and if the depression signs are ignored, it will gradually affect sleep quality. Generally, sleep disturbances are mutually associated with depressive mood and low quality of life. Therefore, to enhance sleep quality and decrease the level of depression in people residing in nursing homes, the necessity of special care programs in the old age should be emphasized. With regard to limitations of this study, we cannot generalize our results to all old population as our study was confined to only 3 districts of Tehran. In addition, since some variables like education and economic status of old age people were not considered in this study, there is a need to generalize the findings. Finally, it is recommended that future studies should investigate the relationship between sleep quality, lifestyle, and daily activities in the nursing homes.